Perspektif Pengembangan Digital Talent Era Industri 4.0 - Veronica Novelia Pretty Puji Hartati; Axel Giovanni (Universitas PGRI Yogyakarta, 2022)
The industrial revolution 4.0 creates a new space for the workforce to be able to compete and compete in the global world. Technological developments in the digital world have given birth to a new paradigm and innovation for employee talent development. This study aims to offer a conceptual framework for digital talent development in the era 4.0. This research was conducted using a literature study method through reference to articles related to the topics discussed. The results of the study found that in facing the industrial era 4.0 where digital transformation occurred, companies need to carry out various programs and policies that support employee talent development such as, training and development, encouraging employee competence, re-skilling, up-skilling. Creating a skilled workforce that is able to adapt to the world is the key to achieving the company's success. In this study, the authors also suggest conducting further empirical and quantitative research on management approaches in the context of industry 4.0. Keywords: digital talent, human resource development, talent management, industry 4.0